Lipodystrophy syndrome associated with antiretroviral therapy in HIV patients: considerations for psychosocial aspects (Revista Latino-Americana de Enfermagem, 2007)
Several side effects have been strongly associated with antiretroviral therapy in HIV patients. Among them, the lipodystrophy syndrome which presents alterations in body shape with central adipose hypertrophy and peripheral lipoatrophy, reported by patients as a visible marker identifying them as HIV patients. This manuscript presents an analysis of current literature regarding the psychosocial aspects of HIV patients with lipodystrophy associated with antiretroviral therapy. The results show that the alterations in body shape can be disturbing in terms of psychosocial well being, affecting quality of life and increasing the stigma associated with the disease, with consequent disturbances in social relations. This analysis provides a preliminary review of the psychosocial aspects of lipodystrophy and further studies are needed for a better understanding of this complex syndrome, which could provide new information to be used in nursing care for HIV patients affected by this problem.